1966
DOI: 10.1139/m66-097
|View full text |Cite
|
Sign up to set email alerts
|

Selenite Reduction by Salmonella Heidelberg

Abstract: When SabwzoncETu h d e l b e r g i s grown in 0.1% w/v Pu'a&Os and examined microscopi~dly during growth, two morpholo~ical changes can be seen. Red intracellular granules arc seen in most of the populatiori within 10 to 12 hours, and organisms containing granules elongate without cell d~vision. The intracellular granuI(:s produced by S. keiddblbcr~ in selenite troth have been identified b!. X-ray analysis as amorphous red r;clenium. The intermediate in the conversion of selenite to elemental selcniun~ has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 6 publications
(1 reference statement)
0
23
0
Order By: Relevance
“…At least some of the SeO 4 2Ϫ -or SeO 3 2Ϫ -respiring bacteria may have the capability to reduce elemental selenium as well (Table 2). Formation of selenide was observed when cells of Salmonella enterica serovar Heidelberg (62) or cell extracts of Micrococcus lactilyticus (63), Clostridium pasteurianum, and Desulfovibrio desulfuricans were exposed to SeO 3 2Ϫ (64). Zehr and Oremland (65) showed that the sulfate-reducing bacterium D. desulfuricans and anoxic estuarine sediments reduce trace amounts of 75 (56).…”
Section: Se 0 -Respiring Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…At least some of the SeO 4 2Ϫ -or SeO 3 2Ϫ -respiring bacteria may have the capability to reduce elemental selenium as well (Table 2). Formation of selenide was observed when cells of Salmonella enterica serovar Heidelberg (62) or cell extracts of Micrococcus lactilyticus (63), Clostridium pasteurianum, and Desulfovibrio desulfuricans were exposed to SeO 3 2Ϫ (64). Zehr and Oremland (65) showed that the sulfate-reducing bacterium D. desulfuricans and anoxic estuarine sediments reduce trace amounts of 75 (56).…”
Section: Se 0 -Respiring Bacteriamentioning
confidence: 99%
“…Several sulfate-reducing bacteria (65,75) and Wolinella succinogenes (76) were reported to reduce significant amounts of SeO 4 2Ϫ under anaerobic conditions without coupling bioreduction to growth. Also, some phototrophic bacteria can reduce SeO 4 2Ϫ in the stationary phase under anaerobic growth conditions (62,64). However, anaerobic respiration appears to be the most environmentally significant process for the selenium cycle (9,15).…”
Section: Mechanisms Of Selenium Oxyanion Reductionmentioning
confidence: 99%
“…Microorganisms that reduce the Se oxyanions SeO 3 2Ϫ and SeO 4 2Ϫ are not confined to any particular group of prokaryotes and are widely distributed throughout the bacterial and archaeal domains (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) Table 1.…”
Section: ϫmentioning
confidence: 99%
“…This may, of course, be the reaction via which glutathione and thioredoxin reductases are involved in the reduction of selenite to elemental selenium in Pseudomonas seleniipraecipitans (71) detailed above. Other reports of the reduction of SeO 3 2Ϫ to Se 0 by bacterial cultures include a detoxification mechanism in Salmonella (38).…”
Section: ϫmentioning
confidence: 99%
“…Some authors have studied and reported these colour changes. McCready et al (1966) reported that orange intracellular granules in bacteria (Salmonella Heidelberg), when grown in the presence of Na 2 SeO 3 , as amorphous red elemental Se. Badii et al in 1986, also observed a deep orange pigment on the undersurface of the A. parasiticus colonies in presence of Na 2 SeO 3 .…”
Section: Effect Of Se Concentration On a Flavus Fc1087 Colony Featuresmentioning
confidence: 99%